Analysis of the energy service in non-interconnected zones of Colombia using business intelligence. Issue 1 (1st January 2021) - Colmenares-Quintero, Ramón Fernando; Maestre-Gongora, Gina Paola; Pacheco-Moreno, Lina Judith; Rojas, Natalia; Stansfield, Kim E.; Colmenares-Quintero, Juan Carlos
Abstract: This work aims to evaluate the provision of energy services in non-interconnected zones (NIZ) between 2018 and 2019 using open data from the Colombian government and business intelligence methodology. The analysis is approached from the ETL (Extract, Transform, Load). It focuses on the variables obtained from the National Monitoring Centre (CNM) for monitoring the operation of these zones, where there is a Telemetry System that provides monthly information on location variables, energy variables, such as active and reactive energy maximum power, maximum power per day, and hours of service delivery. We concluded that in the years, 2018–2019 energy consumption in NIZ has remained stable with a variation of 0.19%. On the other hand, the NIZ include 56% of Colombia's states, and the energy consumption is concentrated in 6 of the 93 municipalities with 80% of national consumption. The challenges in these areas are associated not only with the quality and provision of energy services but also with the environmental challenges that mean that most of these areas obtain their energy supply from fossil fuels, being protected areas such as ecological reserves, the biosphere, or the jungle.